Evaluating Application Integration Success Using DeLone McLean and CSF Model - Al Aziizu Putra Hendriana; Tanty Oktavia (Bina Nusantara University, 2026)
Digital transformation in the financial industry encourages organizations to adopt application integration systems to enhance operational efficiency and effectiveness. However, many information system implementation projects fail to meet expectations, particularly in guarantee institutions characterized by complex business processes. This study evaluates the success of an application integration system project in a guarantee company by applying an integrated framework that combines the DeLone and McLean (D&M) (2003) Information System Success Model with Critical Success Factors (CSF). By explicitly positioning CSF variables as antecedents of system quality, information quality, and service quality, this study extends the conventional use of the D&M model by incorporating managerial and organizational perspectives into the assessment of integration success. A quantitative approach is employed using survey data collected from 120 users of the Penjaminan Application Integration (PAI) system at PT XYZ, which are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that CSF variables—namely top management support, internal communication, user training, and project risk management—significantly influence system quality, information quality, and service quality. Furthermore, these three quality dimensions have a significant effect on intention to use and user satisfaction, which in turn impact perceived net benefits for the organization. In conclusion, integrating managerial and system quality perspectives provides a more comprehensive understanding of application integration project success. These findings offer practical insights for improving IT project implementation strategies in the guarantee sector and in other industries with similar organizational and operational characteristics.